Environmental drivers of ectomycorrhizal communities in Europe's temperate oak forests. Issue 22 (7th November 2014) - Suz, Laura M.; Barsoum, Nadia; Benham, Sue; Dietrich, Hans‐Peter; Fetzer, Karl Dieter; Fischer, Richard; García, Paloma; Gehrman, Joachim; Kristöfel, Ferdinand; Manninger, Miklós; Neagu, Stefan; Nicolas, Manuel; et al.
Abstract Ectomycorrhizal fungi are major ecological players in temperate forests, but they are rarely used in measures of forest condition because large‐scale, high‐resolution, standardized and replicated belowground data are scarce. We carried out an analysis of ectomycorrhizas at 22 intensively monitored long‐term oak plots, across nine European countries, covering complex natural and anthropogenic environmental gradients. We found that at large scales, mycorrhizal richness and evenness declined with decreasing soil pH and root density, and with increasing atmospheric nitrogen deposition. Shifts in mycorrhizas with different functional traits were detected; mycorrhizas with structures specialized for long‐distance transport related differently to most environmental variables than those without. The dominant oak‐specialist Lactarius quietus, with limited soil exploration abilities, responds positively to increasing nitrogen inputs and decreasing pH. In contrast, Tricholoma, Cortinarius and Piloderma species, with medium‐distance soil exploration abilities, show a consistently negative response. We also determined nitrogen critical loads for moderate (9.5–13.5 kg N/ha/year) and drastic (17 kg N/ha/year) changes in belowground mycorrhizal root communities in temperate oak forests. Overall, we generated the first baseline data for ectomycorrhizal fungi in the oak forests sampled, identified nitrogen pollution as one of their major drivers at large scales and revealed fungi that individually and/or in combination with others can be used as belowground indicators of environmental characteristics.